Non-linear modeling and PID control of twin rotor MIMO system - Ramalakshmi, A. P. S.; Manoharan, P. S. (2012 IEEE International Conference on Advanced Communication Control and Computing Technologies, 2012)
This paper deals with PID control tuning for a nonlinear multi-input multi-output system (MIMO). In this paper, a laboratory helicopter model called the twin rotor MIMO system (TRMS) is considered as a MIMO system. The mathematical modeling of helicopter model is simulated using MATLAB/Simulink for controlling it. The two degrees of freedom (2-DOF) are controlled both in horizontal and vertical direction using proportional-integral-derivative (PID) controller. Simulation results are obtained for different input signals. Moreover the error of the plant output and control output of PID controller are presented which show the performance evaluation of TRMS.